Stabilizability for nonlinear difference controls systems with multiple delays - Kanit Mukdasai (2018)
In this paper, we investigate the problem of stabilizability for nonlinear difference controls systems with multiple delays. We present a generalized discrete Gronwall's inequality for stabilizability analysis of this systems. Based on a new Gronwall's inequality, sufficient conditions for stabilizability of this systems are obtained. Numerical examples illustrate the results are given. © ELEMENT, Zagreb.